Madrasah Curriculum Development Based on Pondok Pesantren Through Collaborative Model - M Muhlisin; Muhammad Fajar (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2019)
The purpose of this research is to reveal the process of madrasah curriculum development based on pondok pesantren at MA Al-Ishlah Sendangagung Paciran Lamongan Jawa Timur that consists of curriculum planning, curriculum implementing, and curriculum evaluating. The type of this research was field research and using content analysis techniques. The results of this research summarized that madrasah curriculum development based pondok pesantren should be done by various stages: (1) Curriculum planning carried out by formulating the curriculum content with balanced between general science and religious subjects. (2) Curriculum implementation was combined between MORA, MEC, and KMI curricula, the scopes of the subjects matter in the curriculum were developed more details in religious studies and life skills. (3) Curriculum evaluation implemented based on the achievement of learning outcomes and the attitude of students. (4) Madrasah curriculum development based on pondok pesantren at MA Al-Ishlah Sendangagung Paciran Lamongan Jawa Timur called â€œCollaborative Curriculum Modelsâ€.